Efficient asymmetric TADDOLs-organocatalyzed cycloaddition for the synthesis of allyltin derivatives - Ocampo, Romina Andrea (2014)
We report here the results obtained in the study of organocatalytic asymmetric Diels–Alder reactions to optimize the synthesis of stereo defined allyltin derivatives using (Z)-2-(1-cyclohexenyl)-1-ethenyl(trineophyl)stannane (1) as diene and substituted dienophiles in the presence of (4R,5R)-α,α,α′,α′-tetraphenyl-1,3-dioxolane-4,5-dimethanol (TADDOL, I) and analogs (4R,5R)-α,α,α′,α′-tetra(1-naphtyl)-1,3-dioxolane-4,5-dimethanol (II) and (4R,5R)-α,α,α′,α′-tetra(9-phenantryl)1,3-dioxolane-4,5-dimethanol (III) as chiral catalysts to enhance stereoselectivity through hydrogen bond activation of the dienophile. Catalyst II provided excellent results and ultrasonic radiation at low temperature showed the shorter reaction times.